Designing a Star Schema for Optimizing the Total Sales of Motorcycles - Eka Praja Wiyata Mandala; Randy Permana; Dewi Eka Putri (Journal of Computer Scine and Information Technology, 2021)
Motorcycle sales have increased significantly, motorcycle manufacturers are competing to produce the latest models which are then sold to consumers. As a result, motorcycle dealers are overwhelmed with more and more data, not knowing what to do with it. Motorcycle dealers also have difficulty calculating the total sales of motorcycles. We try to provide solutions to deal with data overflow. We propose designing a star schema as the basis for creating a data warehouse. To create a star schema, we propose a four-step sequence in creating an effective star schema, starting from requirements analysis and reporting, understanding business processes, connecting and matching business processes with suitable entities and determining the dimensions of the business processes. We get a star schema with 1 fact table, motorcycle_sales and 11 of dimension tables, such as brand, color, customer, customer_contract, distributor, district, motorcycle, repair_workshop, sell_location, type and time. The star schema is an optimized model that provides the best performance in presenting more complex information